Penerapan Simulasi-Role Playing dalam Pembelajaran PAI untuk Meningkatkan Kebiasaan Positif Siswa Kelas VII di SMPN 2 Karawang Timur - Hendra Asri Harahap; Elisa Wulandari; Fahmi Lestari Prasetiadi; Hana Fauziyah; Khaila Najwa Saefina (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to implement the simulation-role playing method in fostering students' positive habits towards the social environment in learning the material of ghibah implementing tabayun in class VII students at SMPN 2 East Karawang. The research was conducted through two cycles, where each cycle included four stages, namely: planning, action implementation, observation, and reflection. Data collection was carried out using an instrument in the form of a multiplechoice test of 20 questions that focused on the material of avoiding gibah and carrying out tabayun. The data obtained were analyzed descriptively quantitatively to determine the improvement of student learning outcomes. The Minimum Completeness Criteria (KKM) set in this study is 70. This study is considered successful if at least 70% of all students get a score ≥70. This finding shows that the use of the Simulation-Role Playing method is effective during learning and fosters positive habits towards the social environment. Thus Simulation-Role Playingf can be a relevant alternative in learning Islamic Religious Education at the junior high school level.